2006
DOI: 10.1242/jcs.03018
|View full text |Cite
|
Sign up to set email alerts
|

Active and passive displacement of transmembrane domains both occur during opsin biogenesis at the Sec61 translocon

Abstract: We used a site-specific crosslinking approach to study the membrane integration of the polytopic protein opsin at the endoplasmic reticulum. We show that transmembrane domain 1 occupies two distinct Sec61-based environments during its integration. However, transmembrane domains 2 and 3 exit the Sec61 translocon more rapidly in a process that suggests a displacement model for their integration where the biosynthesis of one transmembrane domain would facilitate the exit of another. In order to investigate this h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
61
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(74 citation statements)
references
References 37 publications
(104 reference statements)
12
61
1
Order By: Relevance
“…Of the membrane-associated products recovered, 8% were Nglycosylated for the control sample (lane 4). Lower molecular weight forms of non-glycosylated Sec61␤ were more prevalent after RNC preparation (lanes 1-6, product 0g and below), most likely as a result of ribosome stacking (Ismail et al, 2006). We confirmed that EDTA treatment does not prevent N-glycosylation per se (data not shown), hence, a lack of glycosylated Sec61␤ reflects a lack of integration.…”
Section: Purified Chaperones Can Facilitate Sec61␤ Integrationsupporting
confidence: 66%
“…Of the membrane-associated products recovered, 8% were Nglycosylated for the control sample (lane 4). Lower molecular weight forms of non-glycosylated Sec61␤ were more prevalent after RNC preparation (lanes 1-6, product 0g and below), most likely as a result of ribosome stacking (Ismail et al, 2006). We confirmed that EDTA treatment does not prevent N-glycosylation per se (data not shown), hence, a lack of glycosylated Sec61␤ reflects a lack of integration.…”
Section: Purified Chaperones Can Facilitate Sec61␤ Integrationsupporting
confidence: 66%
“…It has been shown by chemical cross-linking that a close proximity to Sec61␤ is one of the early events during TM domain integration (40,41). The cross-links with Sec61␤ disappear once the TM domain moves laterally into the membrane, as evident from enhanced lipid cross-links and glycosylation of a tag N-terminal to the TM domain (38,42).…”
Section: Discussionmentioning
confidence: 99%
“…Although a single heterotrimer is suggested to form the proteinconducting channel through the membrane, it is likely that several Sec61 heterotrimers assemble in the active ER translocon together with multiple accessory components, including TRAM (translocating chain-associated membrane protein), the TRAP complex and PAT-10, during membrane protein integration (Hegde and Kang, 2008). Such an arrangement might contribute to the translocon architecture required to allow the simultaneous accommodation of multiple TM segments during membrane protein biosynthesis (Ismail et al, 2006;Kida et al, 2005;Sadlish et al, 2005).…”
Section: Introductionmentioning
confidence: 99%